Combining sukuk with waqf for socio-economic development - Mohd. Zain, Nor Razinah; Syed Azman, Syed Marwan Mujahid; Engku Ali, Engku Rabiah Adawiah (Cambridge Institute of Islamic Finance (Cambridge-IIF), 2020)
Sukuk is one of investment securities generated from Islamic capital market (ICM) which receives a direct and an indirect influence from the growth of Islamic financial services industry around the globe. Currently, the growth of Sukuk is expected to recover in 2019 by rising up to US$87 billion after its slight declination to US$78 billion in 2018. It is forecast to raise towards US$100 billion in 2020 as reported by Moody’s Investors Service (The Edge Market, 2019). The growth of Sukuk was decreasing due to lesser issuances of global sovereign and supranational Sukuk. It also receives an impact from the fluctuated of oil prices. Such situation resulted to a declined of the issuances of global sovereign Sukuk by five per cent in 2018.